ANALYSIS OF STRUCTURAL TRANSFORMATION OF LABOR FROM AGRICULTURE TO NON-AGRICULTURE IN ASIA - Emy Zahrotul Awaliyyah; Shwu-En Chen; Ratya Anindita; S Suhartini (Agricultural Socio-Economics Journal, 2020)
Through the dataset from APO (Asian Productivity Organization) comprising 22 countries in Asia from 1980 to 2015, this study is to investigate the growth pattern, decomposition, and determinants of structural transformation in Asia. A decomposition method measuring within-effect, between-static-effect, and between-dynamic-effect was adopted to explain the structural change within sectors of agriculture, industry, and services.  The results show that the agriculture sector of all countries in Asia declines slowly. The agriculture sector is no longer the largest contributor to GDP in all Asian countries even though it still has the largest labor in Asian developing countries. Workers moving from the agriculture sector to the services sector as the productivity of the service sector is higher than agriculture. The structural changes positively contribute to productivity growth in Asia as a result of the positive static reallocation effects and negative dynamic reallocation effects. Overall, the structural changes contribute to a large part of labor productivity growth. The important determinants of structural transformation are the employment share in agriculture and trade. Final, the policy implication was proposed for structural changes.